Photovoice in the EFL classroom: Academic stress coping among Indonesian Pre-Service English teachers during online learning - Zaenal Anwar, Muhammad; Wahyuningsih, Sri (Universitas Lancang Kuning, 2024)
The pandemic impacted people's lives worldwide, affecting the functioning of several sectors, especially in the education sector. The impact of the pandemic has resulted in teachers and students having to work faster and maximize learning from face-to-face to online learning. The impact is that some students or teachers experience difficulties and stress in online learning. This stress is a person's thoughts that were originally (positive) to be irrational/negative. The purpose of this study is to describe experiences dealing with academic stress among pre-service English teachers in Indonesian higher education during online learning. The authors used the photovoice method by explaining some photos in this article. We also interviewed four pre-service English teachers to get more data. The findings revealed that some ways used by pre-service English teachers in coping with academic stress during online learning are playing online games, having extensive reading such as comics, relaxation or healing, and listening to music. The study promotes an implication that the need to have some refreshments for students to cope with academic stress during online learning during the COVID-19 pandemic.